The Effectiveness of Teaching Listening Skills through English Movies - Usman, Abdurrahman Hi.; Ajam, M. Ridha; Tegamuni, Suhaimi (Universitas Negeri Makassar, 2025)
Teaching English skills requires effective techniques of teaching and teaching media. One of them is movies. This study explores and describes the effectiveness of teaching listening skills through English movies. The objectives of this study are to (1) analyze the description of listening skills through English movies as the media of learning; (2) analyze the description of listening skills without English movies as the media of learning; (3) analyze the effectiveness of the listening skills learning through English movies and without English movies as the media. The study was designed in experimental research employing experimental and control groups of students as the subjects of the study. Each group was treated using different techniques. The treatment began with the pre-test and ended with the post-test as the data collection technique. The instruments used written and oral test items. The data collected were analyzed quantitatively. Based on the data, it was concluded that (1) the average N-gain score for the experimental group is 61% indicating that teaching listening skills using English films is included in the category effective enough; (2) the average N-gain score for the control group is 38%, the N-gain score is at least 0.00% and a maximum of 64.29% indicating that teaching listening skills without using films in English is included as the ineffective category; (3) there is a difference between average learning outcomes in teaching listening skills using English films and teaching listening skills without using English films (conventional).